Using the Very Short Form of the Children's Behavior Questionnaire for Spanish-Speaking Populations in Low- and Middle-Income Countries: A Psychometric Analysis of Dichotomized Variables - Elsa Lucia Escalante-Barrios; Sonia Mariel Suarez-Enciso; Samuel P. Putnam; Helen Raikes; Sergi Fàbregues (MDPI AG, 2021)
While the psychometric properties of the Spanish version of the Very Short Form of the Children's Behavior Questionnaire (CBQ-VSF) have been assessed in the US and Europe in samples composed of middle- and high-income parents with high levels of education, no studies have tested the instrument in low-income Spanish-speaking populations living in low- and middle-income countries. To fill this gap, our cross-sectional study assessed the psychometric properties of the Spanish version of the CBQ-VSF version in a sample of 315 low-income and low-educated parents with preschool children living in the Caribbean Region of Colombia. While our findings revealed problems that were similar to those identified in previous assessments of the CBQ-VSF Spanish version, they also showed unique problems related to the sociodemographic characteristics of our sample, containing many individuals with a low income and low educational level. Most of the participants gave extreme responses, resulting in a notable kurtosis and skewness of the data. This article describes how we addressed these problems by dichotomizing the variables into binary categories. Additionally, it demonstrates that merely translating the CBQ-VSF is insufficient to be able to capture many of the underlying latent constructs associated with low-income and low-educated Latino/Hispanic populations.